Improvement of Current Reading Abilities Through Letter Card Games for Class 2nd SD Students - Nita Rusiana (Universitas Sebelas Maret, 2020)
The purpose of this research is that students can read simple words and sentences fluently and accurately through letter card games. The research conducted was a Classroom Action Research (PTK) in three cycles. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting is carried out a pre test and post test to determine the progress of students. In the first cycle, the students who completed after carrying out the post test were 73.3%. In cycle II students who completed after carrying out the post test were 90%. These results indicate that reading fluently through the letter card game can improve student learning outcomes, especially Indonesian language muple at SDN 02 Kebagusan.